ANALISIS KEMAMPUAN LITERASI MATEMATIKA SISWA KELAS IX SMP NEGERI 6 MEDAN DITINJAU BERDASARKAN GENDER - Alyu Witriamay Fhutu Neva; Nurhasanah Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the mathematical literacy skills of male Grade IX students SMP Negeri 6 Medan, to describe the mathematical literacy skills of female Grade IX students SMP Negeri 6 Medan, and to determine the level of achievement of mathematical literacy skills of Grade IX students SMP Negeri 6 Medan. This research is a descriptive qualitative study. The subjects of this research were 26 students of class IX-K at SMP Negeri 6 Medan in the academic year 2025/2026. Data collection in this study was carried out through mathematical literacy tests and interviews. The results of the study show: (1) Male students had average percentage scores on three indicators of mathematical literacy, namely understanding (43.33%), application (50%), and reasoning (8.33%). (2) Female students had average percentage scores on three indicators of mathematical literacy, namely understanding (68.18%), application (81.82%), and reasoning (40.91%). (3) The achievement level of mathematical literacy skills for female students was 61.11%, which falls into the ‘fair’ category, while the achievement level for male students was 47.22%, which falls into the ‘poor’ category.